2015
DOI: 10.1007/s00520-015-2967-3
|View full text |Cite
|
Sign up to set email alerts
|

A randomised trial of the cool pad pillow topper versus standard care for sleep disturbance and hot flushes in women on endocrine therapy for breast cancer

Abstract: This study supports the use of the CPPT as an aid to reduce sleep disturbance and the frequency/severity of hot flushes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 43 publications
0
9
0
1
Order By: Relevance
“…These symptoms have also been proposed to have an additive effect whereby when men wake up due to night doi: 10.18282/amor.v2.i2.94 sweats, they may also empty their bladder, thus prolonging the length of time they are awake at night and possibly making it more difficult to resume sleep [47] . Some men can adapt to the adverse effects of ADT [47] ; however, the management of insomnia may be improved by treating adverse treatment side effects with greater use of interventions such as the cool pad pillow topper, which reduces the frequency/severity of hot flushes and sleep disturbance among women, and a greater use of incontinence medication (e.g., tolterodine) [47,63] . Men with a personal and/or family history of insomnia, those who experience distress, anxiety and/or depression, and men with later stages of cancer are at an increased risk of insomnia.…”
Section: Discussionmentioning
confidence: 99%
“…These symptoms have also been proposed to have an additive effect whereby when men wake up due to night doi: 10.18282/amor.v2.i2.94 sweats, they may also empty their bladder, thus prolonging the length of time they are awake at night and possibly making it more difficult to resume sleep [47] . Some men can adapt to the adverse effects of ADT [47] ; however, the management of insomnia may be improved by treating adverse treatment side effects with greater use of interventions such as the cool pad pillow topper, which reduces the frequency/severity of hot flushes and sleep disturbance among women, and a greater use of incontinence medication (e.g., tolterodine) [47,63] . Men with a personal and/or family history of insomnia, those who experience distress, anxiety and/or depression, and men with later stages of cancer are at an increased risk of insomnia.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, we established a connection between insomnia and pain, depression, anxiety and/or a reduced quality of life [ 27 , 43 , 53 , 54 , 58 , 63 , 64 , 65 ]. Various types of treatments for insomnia include pharmacological therapies (e.g., hypnotica, sedativa, antidrepressiva, neuroleptics, antihistamine, hormones (melatonin) and herbal extracts) [ 28 , 30 , 42 , 44 , 48 , 57 ] and nonpharmacological therapies (like Psychoeducational intervention, Cognitive Behavior Therapy (CBT), Professionally administered CBT (PCBT), Video-based CBT (VCBT), Behavioral Therapy (BT), Individualized Sleep Promotion Plan (ISPP), Mindfulness-Based Stress Reduction (MBSR), Valencia model of Waking hypnosis, Internet intervention/Sleep Healthy Using The internet (SHUTi), Progressive Muscle Relaxation (PMR), Autogenic Training (AT), (Electro)Acupuncture (EA), Tai Chi Chih (TCC), Cool Pad Pillow Topper (CPPT), Combined multimodal-aerobic Treatment (CT), Multimodal Treatment (MT) and Aerobic Treatment (AeT)) [ 29 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 44 , 46 , 47 , 49 , 50 , 51 , 52 , 55 , 56 , 57 , 59 , 61 , 62 , 66 , 67 , 68 , 69 , 70 ...…”
Section: State-of-the-artmentioning
confidence: 99%
“…Sleep disturbances/disorders and excessive daytime sleepiness (EDS) have been reported to influence fatigue [ 1 , 2 , 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 ] and its perceptions. Savard et al studied cancer survivors and showed that 52% of them reported sleeping difficulties, and 58% reported that cancer either caused or aggravated their sleeping problems [ 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , <...>…”
Section: Introductionmentioning
confidence: 99%
“…Nezvyklým prostředkem k ovlivnění poruch spánku v souvislosti s výskytem návalů horka jsou chladicí polštáře. Letos byly publikovány výsledky randomizované klinické studie, která prokázala benefit jejich použití v terapii nejenom poruch spánku, ale i v ovlivnění hot flashes [63]. Přestože jsou poruchy spánku uváděny jako jeden z vedlejších účinků terapie esci-infekce.…”
Section: Poruchy Spánkuunclassified